2021
DOI: 10.32802/asmscj.2021.819
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles and Academic Achievement among Form Three Living Integrated Skills Students

Abstract: Learning styles indicate a students’ preference for learning methods and therefore are necessary information to guide teachers’ instruction. This study is aimed to determine the relationship between learning styles and academic achievement of Form Three students in their Living Integrated Skills subject. This study was participated by 372 respondents selected using purposive sampling from six secondary schools in Sabah, Malaysia. Data was collected using a research questionnaire in survey research and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In contrast, a study of Malaysian students found that the theoretical learning style has the strongest connection to academic performance, followed by reflective and pragmatic, and the weakest learning style is activist. Likewise, factors such as the classroom environment, delivery of instruction, and student self-efficacy are important predictors of learning [49].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study of Malaysian students found that the theoretical learning style has the strongest connection to academic performance, followed by reflective and pragmatic, and the weakest learning style is activist. Likewise, factors such as the classroom environment, delivery of instruction, and student self-efficacy are important predictors of learning [49].…”
Section: Discussionmentioning
confidence: 99%